Anti-semitism in France : a political history from Léon Blum to the present - Birnbaum, Pierre 1940- (Studies in social discontinuity, 1992)
When the French Revolution promised the citizens of France liberty and equality, the Jews were not excluded. The Jews enjoyed full rights of citizenship in France long before they did in other countries, such as Germany or England. In the nineteenth and early twentieth centuries there were Jews in the highest ranks of the French civil service and government, and in 1936 Leon Blum became prime minister. Such men as Blum and, later, Pierre Mendes France, were known as Juifs d'Etat ('state Jews'). But with their rise to power came a new form of anti-Semitism. To the traditional vilification of the Jew as a wanderer, a sexual deviant and a usurer, was added the myth of the double-dealing statesman--one who used political power and position to undermine the strength and strip away the wealth of the true France ('la vraie France eternelle'). Such views predated the Dreyfus case, became acute under the Vichy regime, and persist today, as recent incidents of political and social anti-Semitism in France show so clearly. Pierre Birnbaum here provides an account of the origins, history and effects of anti-Semitism. He refers to and quotes from original source material, much of it previously unknown, and uses press reports, interviews and scurrilous verses to illustrate his theme--that there is a cancer at the heart of French society which has not yet been fully excised.